Assessing the disproportionality of depressive reactions to life stress. (25th October 2021) - Pfeifer, Benjamin J.; Strunk, Daniel R.
Abstract: Background: Prior to DSM‐5, depression had long been conceptualized as symptoms without cause or disproportionate to one's circumstances. A central challenge to considering whether a depressive reaction is disproportionate is the lack of measures assessing disproportionality. Drawing on a study of patients participating in cognitive behavioural therapy for depression, we evaluate two new measures of the disproportionality of one's depressive symptoms to their recent life circumstances. Methods: To assess the disproportionality of depressive symptoms, we developed an interview‐based assessment and a brief self‐report measure. We employed both assessments in a sample of 126 patients who participated in cognitive behavioural therapy for depression. Results: Initial evidence for the reliability and validity of both self‐report and interview‐based approaches appeared promising. Interview judges demonstrated strong inter‐rater reliability on life stress ratings, and both forms of disproportionality showed a pattern of correlations with variables reflecting greater clinical complexity, including self‐reported personality dysfunction and symptom severity. Comorbid generalized anxiety disorder (GAD) was the only previously proposed marker of complicated depression to significantly predict both disproportionality scores. Limitations: The sample had limited ethnic diversity and tended to be highly educated. Participants all met criteria for major depressive disorder and sought treatment. Conclusions: Two assessments of the disproportionality of depressive reactions demonstrated evidence of reliability and validity. Despite limited efforts at assessment to date, these results suggest these measures may be able to reliably distinguish the disproportionality of depressive reactions and allow clinicians to better assess contextual life stress depressive disorders.